Legislation for effective post‐disaster reconstruction - Rotimi, James Olabode; Wilkinson, Suzanne; Zuo, Kelvin; Myburgh, Dean (International Journal of Strategic Property Management, 2009)
New Zealand is vulnerable to natural disasters. When disasters occur, the effects can be devastating on the built environment. As one aspect of a major programme of research in New Zealand, the authors address the recovery issue in terms of how legislation either facilitates or hinders reconstruction. The results of a survey to building control officers and other disaster practitioners in New Zealand on the application of the Building Act 2004 post‐disaster are presented in this paper. There are indications that the New Zealand Building Act 2004 will not be supportive or enabling in post‐disaster reconstruction environments, particularly in large‐scale disaster events. Key problems found were procedural constraints as a result of high consenting standards and logistic considerations. The desire is to create the best possible conditions that will encourage rapid rebuilding of lives and communities after large‐scale disasters in New Zealand and that can only be done within a supportive legislative environment.First Publish Online: 18 Oct 2010